Selecting stage ypT0–1N0 for locally advanced rectal cancer following preoperative chemoradiotherapy: implications for potential candidates of organ‐sparing management. (October 2016) - Huang, S. H.; Chi, P.; Lin, H. M.; Lu, X. R.; Huang, Y. W.; Xu, Z. B.; Sun, Y. W.; Ye, D. X.; Wang, X. J.; Wang, X.
Abstract: Aim: Local excision or a wait‐and‐see policy may offer the possibility of organ preservation for locally advanced rectal cancer (LARC) after preoperative chemoradiotherapy (CRT). Identifying associated factors of good responders (GR) with stage ypT0–1N0 would probably influence the selection of potential candidates who were theoretically eligible for organ‐sparing management. This study was to establish a scoring system to select stage ypT0–1N0 for LARC following preoperative CRT. Method: Between 2009 and 2014, 262 patients with middle and low LARC were treated with CRT and radical surgery. Clinicopathological data which were found to be significantly associated with GR were incorporated into a scoring system. Results: Fifty‐seven (21.8%) patients were GR with stage ypT0–1N0 in the operative specimen. Multivariate analyses indicated that a low level of pretreatment carcinoembryonic antigen (CEA) and post‐treatment CEA <2.55 ng/ml ( P  =   0.008 and P  =   0.009 respectively) and long‐axis diameter of residual tumours ( P  =   0.006) were independently associated with stage ypT0–1N0. The three factors were incorporated into a scoring system. Using receiver operating characteristic curve analysis, we determined a cutoff value of −0.3 for scores, at which the system's sensitivity was 71.9% and specificity 73.1%. When applied to testing samples, the sensitivity was 74.1% and specificity 76.2%. Conclusion: We demonstrated that low levels of pretreatment and post‐treatment CEA and the long‐axis diameter of residual tumours were associated with stage ypT0–1N0 for LARC after CRT. Therefore, the three‐factor scoring system may be used to select potential candidates for organ‐sparing management.